Snapshots in Review - Kmetz, Karla (Disability Studies Quarterly, 2008)
During the Summer of 2006, Karla Kmetz and Professor Brenda Brueggemann created a multimedia web portfolio that captures pieces of disability history at The Ohio State University. This article documents the research experience, creation process, and revisions to the project.